Photocatalytic Plasmon‐Enhanced Nitrogen Reduction to Ammonia. Issue 3 (1st February 2021) - Monyoncho, Evans A.; Dasog, Mita
Abstract : Nitrogen reduction to ammonia under ambient conditions is an emerging area of research sparked by the increasing concerns over climate change which is driving the efforts to find alternatives to energy‐intensive Haber–Bosch process. Ammonia is a critical component in the manufacturing of fertilizers and is required to support the global food supply. It can also be used as a fuel source to generate electricity. Many strategies have been used to drive nitrogen reduction under milder conditions including incorporation of plasmonic nanomaterials. The ability of plasmonic nanomaterials to strongly interact with light, resulting in near‐field enhancement, hot charge‐carrier generation and injection, increase in local temperature, has made them attractive candidates for catalysis. This review provides a comprehensive survey of recent developments in photocatalytic, plasmon‐enhanced nitrogen conversion to ammonia and the proposed mechanisms for the increased catalytic activity. A brief outlook on the current challenges and future directions is also provided. Abstract : Plasmonic nanomaterials are attractive candidates for catalysis as they strongly interact with light, resulting in near‐field enhancement, hot charge‐carrier generation and injection, and increase in local temperature. This review provides a comprehensive survey of plasmonic nanomaterials used in a photocatalytic conversion of nitrogen to ammonia and the proposed mechanisms for the enhanced activity.